ESTUDO DO POTENCIAL DE MERCADO DE HORTALIÇAS ORGÂNICAS NO MUNICIPIO DE SANTA ROSA - SELES, ANDRÉIA R.; OLSSON, GIZELA; SEVERO, LEANDRO; WESCHENFELDER, MICHAEL; PRESCHADT, RAFAEL; ZAMBERLAN, LUCIANO (Salão do Conhecimento, 2013)
Resumo